Adverse outcome in follicular lymphoma is associated with MYC rearrangements but not MYC extra copies. (21st June 2021) - Bussot, Lucile; Chevalier, Simon; Cristante, Justine; Grange, Béatrice; Tesson, Bruno; Deteix‐Santana, Clémence; Orsini‐Piocelle, Frédérique; Leyronnas, Cécile; Dupire, Sophie; Gressin, Rémy; Salles, Gilles; Bachy, Emmanuel; et al.
Summary: Follicular lymphomas (FLs) with MYC rearrangements ( MYC ‐R) and extra copies of MYC ( MYC ‐EC) are rare and the prognosis impact is uncertain. We conducted a retrospective study including 321 FL patients, among whom 259 (81%) had no 8q24 alterations and 62 (19%) were assigned to 8qAlt. Forty‐five cases were classified as MYC ‐EC and six as MYC ‐R. MYC ‐R patients were significantly older ( P  = 0·008), had higher follicular lymphoma international prognostic index (FLIPI) stage ( P  = 0·05) and β2‐microglobulin (β2m; P  = 0·05). Among patients treated with immuno‐chemotherapy, four presented a MYC ‐R and 25 a MYC ‐EC. Univariate analysis showed the absence of significant difference between MYC ‐EC and normal MYC ( MYC ‐NL) regarding progression‐free survival (PFS; HR1·3; 95% CI [0·4–1·6]) and specific overall survival (SOS; HR 1·6; 95% CI [0·4–5·7]). Those results were compared to data from the PRIMA trial. This confirmed that MYC ‐EC had no impact on PFS ( P  = 0·86) or SOS ( P  = 0·9). Conversely, MYC ‐R was associated with a trend to inferior outcome regarding PFS (HR : 6·1; 95% CI [2·2–17·1]; P  = 0·00026), lymphoma‐related death (SOS; HR 13·6; 95% CI [2·9–65]; P  = 0·00014) and risk of transformation (transformation‐free survival (TFS); HR 82·7; 95% CI [14·8–463·4]; P  < 0·0001). In conclusion, MYC ‐EC has no prognostic impact in FL but MYC ‐R FL tended to be associated with an increased risk of transformation and poorer outcome.